Correlation between clinical tests for gait and stability using biomechanical variables in the gait of institutionalized elderly subjects - Palma Felipe H.; Rodríguez Sebastián Cisternas; Buton Francisco Vargas; Nieva Marcela Olmos; Redenz Günther; Guzmán-Venegas Rodrigo (Sciendo, 2021)
Study aim: This study aims to identify biomechanical gait variables explaining clinical test results in institutionalized elderly people.